2020
DOI: 10.3390/plants9121670
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Tissue Localization of Selenium in Rice (Oryza sativa L., Poaceae) Grains: A Perspective of Agronomic Biofortification

Abstract: In worldwide production, rice is the second-most-grown crop. It is considered a staple food for many populations and, if naturally enriched in Se, has a huge potential to reduce nutrient deficiencies in foodstuff for human consumption. This study aimed to develop an agronomic itinerary for Se biofortification of Oryza sativa L. (Poaceae) and assess potential physicochemical deviations. Trials were implemented in rice paddy field with known soil and water characteristics and two genotypes resulting from genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The agronomic management of trials, namely the application of nitrogen fertilizers, control of weeds, insect pests and diseases and the water management (irrigation) were those recommended and typically used for the rice crop in this region. Furthermore, the accurate characterization, regarding soil characteristics and irrigation water, of the studied area was identical to that described in a previous and recently published work [ 42 ], where some climate parameters were also taken into account.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…The agronomic management of trials, namely the application of nitrogen fertilizers, control of weeds, insect pests and diseases and the water management (irrigation) were those recommended and typically used for the rice crop in this region. Furthermore, the accurate characterization, regarding soil characteristics and irrigation water, of the studied area was identical to that described in a previous and recently published work [ 42 ], where some climate parameters were also taken into account.…”
Section: Methodsmentioning
confidence: 92%
“…Two different cultivars of rice were submitted to foliar fertilization by various concentrations of selenite and selenate (25, 50, 75 and 100 g Se.ha −1 ) at different stages of rice development, i.e., booting, anthesis and milky grain phase. After harvest a 4.9–7.1-fold increase in Se content was observed in grain from plants sprayed with selenate, while a 5.9–8.4-fold increase was noted for selenite [ 42 ]. These findings are in agreement with previous reports using four rice genotypes (Ariete, Albatros, OP1105 and OP1109) in field trials with foliar fertilization ranging between 0 and 300 g Se.ha −1 for sodium selenite and sodium selenate [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that there are two ways to improve the selenium content of rice: one is to improve the content of Se in rice by exogenous application of selenium, the other one is breeding of selenium-rich rice varieties [10,14,32,36,55]. Zhang et al [56] studied 151 rice varieties before finding that brown rice contained selenium ranging from 0.029 mg kg −1 to 0.103 mg kg −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Many levels of selenium fertilizer were studied to produce Se-rich rice [10,20,37], and the concentrations of foliar fertilizers ranging between 25 and 100 g Se ha −1 did not surpass the threshold of toxicity [10]. Therefore, there was a division of the treatment into three groups: 0 g Se ha −1 (L0), 40 g Se ha −1 (L1), and 80 g Se ha −1 (L2) in this study.…”
Section: Field Experimentsmentioning
confidence: 99%
See 1 more Smart Citation